2021
DOI: 10.21037/tcr-20-2908
|View full text |Cite
|
Sign up to set email alerts
|

High pretreatment plasma D-dimer levels predict poor survival in patients with diffuse large B-cell lymphoma in the real world

Abstract: Background: Data on the role of pretreatment plasma D-dimer levels in the prognostic prediction of patients with diffuse large B-cell lymphoma (DLBCL) are limited. We here studied the potential prognostic roles of pretreatment plasma D-dimer levels in patients with DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…A total of 13 studies 1 , 6 , 7 , 16 , 19 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 were included in our study (PRISMA flow diagram) based on the searched databases. Overall, eight studies 1 , 6 , 7 , 37 , 39 , 40 , 41 , 43 focused on the role of RDW and the remaining five studies 16 , 19 , 36 , 38 , 42 focused on D‐Dimer levels in DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 studies 1 , 6 , 7 , 16 , 19 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 were included in our study (PRISMA flow diagram) based on the searched databases. Overall, eight studies 1 , 6 , 7 , 37 , 39 , 40 , 41 , 43 focused on the role of RDW and the remaining five studies 16 , 19 , 36 , 38 , 42 focused on D‐Dimer levels in DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
“…All included articles were retrospective cohorts. Eight studies were conducted in China 7 , 16 , 19 , 36 , 38 , 39 , 40 , 43 and others were conducted in Croatia, 41 Iraq, 37 Japan, 42 Peru, 1 and Spain. 6 The total sample size of the meta‐analysis was 3972 people (1252 and 2720 patients in the studies were related to prognostic roles of D‐Dimer and RDW in DLBCL patients, respectively) varying from 81 to 992 people in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies (1,6,7,16,19,(36)(37)(38)(39)(40)(41)(42)(43) were included in our study (PRISMA flow diagram) based on the searched databases. Overall, eight studies (1,6,7,37,(39)(40)(41)43) focused on the role of RDW and the remaining five studies (16,19,36,38,42) focused on D-Dimer levels in DLBCL patients. The included studies were published from 2015 to 2022.…”
Section: Resultsmentioning
confidence: 99%
“…As a degradation product of fibrin, elevated D-dimer could reflect high activation of coagulation and fibrinolysis, which was supposed to be related with poor OS of DLBCL. 10,11 Furthermore, CRP is one of the standard markers that reflect objective inflammation 12 and it has shown that elevated CRP has a negative prognostic impact on DLBCL. 13 Inadequate diet and proliferation of tumor cells have contributed to malnutrition in cancer patients, which in turn leads to poor response to treatment.…”
Section: Introductionmentioning
confidence: 99%